(3GdJcJdGJ GdEbJUGOjI GdEbdjejI aj EWGQ GdYhdeIs - (3SejQ eMeO(B, (3YHO GdYRHRs ((3GdEScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2006)
(3GdchejSG(B- (3eLehYI (B15 -(3ChQhHG GdehMOI(B- (3GdeTGQcI GdCQhHjI GdEaQjbjI GdeJhSWjI(B- (3efWbI GdJLGQI GdYQHjI GdMQIs
Keywords: (3GdEbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs; (3GdJcJdGJ GdEbJUGOjI (B- (3GdOhdjIs; (3GdYhdeIs